교번스퍼터링법에 의해 다양한 기지상 재료위에 형성된 Au 나노입자의 성장거동에 대한 전기, 광학적 분석 - 김범준; Bum-joon Kim; 김현철; Hyun Chul Kim; 박종건; Jong-geon Park; 이경석; Kyeong-seok Lee (대한금속·재료학회지, 55(10), 2017)
Nanocomposite films, which are comprised of metal nanoparticles dispersed in a matrix layer, have attracted great interest due to their unique electrical and optical properties, which are mainly due to the excitation of localized surface plasmons. In this study, we employed an alternating sputtering method to fabricate such nanocomposite films. We then systematically investigated the effect of SiO 2 , (Ba,Sr)TiO 2 , and Si matrix materials on the growth behavior of Au nanoparticles and their geometric distribution, which strongly affects their plasmonic properties, using both electrical and optical means. From the results, we suggest an effective way of monitoring the growth stages of Au nanoparticles and adjusting their geometric distribution to a desired form, by properly selecting the combination of materials and process controls. (Received May 16, 2017; Accepted June 17, 2017)